Strategies Overcome Barrier between Doctor and Patient Communication at National Heart Institute, Malaysia - Vimala, Govindaraju; Aizai Azan, Abdul Rahim (Institute of Medico-Legals Publications, 2020)
The relationship between doctors and patients is broadly concerned and discussed in health care aspect. The objective of this study focused on the strategies how cardiologists overcome the barrier during communicate with patients using interpersonal communication (IPC) skills. Qualitative research methodology and a phenomenological approach was applied in this study through in-depth interview and observation sessions with 8 cardiologists. The gathered data were transcribed verbatim and analysed it using ATLAS.ti7 software in the way to identified the key themes, sub-themes and inter-relationships on the quotes. The results of the study showed it is recommended a doctor should be trained on managing time while the consultation session take place with patients and for doctors’ time limitation really challenge to serve the patients. Through time management training it is possible for the doctors may more effectively and efficiently communicate with patients during the consulting session